PENYULUHAN KESEHATAN TENTANG HIV/AIDS PADA REMAJA DI SMP SATAP NEGERI 3 SAUSU KECAMATAN SAUSU KABUPATEN PARIGI MOUTONG - Veni Mornalita Kolupe; Niluh desy purnamasari; Ni kadek Armini (AMMA : Jurnal Pengabdian Masyarakat, 2022)
During adolescence, changes occur both physically, psychologically and socially. Physical changes that occur include the development and maturation of the reproductive organs. Psychological changes result in changes in attitudes and behavior, such as starting to pay attention to one's appearance, starting to be interested in the opposite sex, trying to attract attention and feeling love, which will then arise sexual urges. Socially in their development, adolescents are very vulnerable to environmental influences, negative social and cultural environments are risk factors for adolescents to be trapped in risky behaviors such as sexuality, HIV/AIDS and drugs (TRIAD KRR) which have an impact on their health conditions. Free sex behavior will bring various negative impacts on the lives of adolescents themselves, for example Sexually Transmitted Diseases (STDs), HIV/AIDS and Unwanted Pregnancy (KTD). One of the consequences of unwanted pregnancy is abortion. Based on data from the Indonesian Family Planning Center (PKBI) in 2018, no less than 2.5 million abortion cases were found in Indonesia every year. Ironically, 21.2% of abortionists are teenagers, and most of them are carried out in an unsafe way. About 30-35% of these abortions are a contributor to maternal mortality. HIV/AIDS if it occurs in adolescents not only affects physically, but also affects mental health, emotions, economic conditions, and social welfare in the long term. nation in the end. This is because teenagers are part of the human resource component which is a very valuable asset for the nation in the future. This community service in general is to assist the government in improving the quality of youth free from TRIAD KRR (sexuality with STDs, HIV and AIDS and drug problems) through promotional/preventive efforts about the importance of healthy reproductive organs, curative efforts through examination of adolescent reproductive health in junior high schools. SATAP Negeri 3 Sausu in Sausu District, ParigiMoutong Regency.